Keratinocyte cancer with incidental perineural invasion: A registry analysis of management and 5‐year outcomes. (13th April 2020) - Adams, Agnieszka; De'Ambrosis, Brian; Panizza, Ben; Belt, Paul; Emmett, James; Warren, Tim; Whiteman, David C.
Abstract: Background/Objectives: Perineural invasion within keratinocyte cancer is a hallmark of tumour aggression, and a definitive treatment paradigm for this condition remains undetermined. Our aim was to investigate the treatment and outcomes of keratinocyte cancer with incidental perineural invasion within two skin cancer databases to refine treatment protocols. Methods: We retrospectively assessed the Queensland Perineural Invasion Registry for surgery, histopathology, adjuvant radiotherapy and recurrence of keratinocyte cancer five years post‐definitive treatment. We also reviewed the Princess Alexandra Hospital Head and Neck clinical perineural invasion database, specifically looking at surgical margins and adjuvant radiotherapy of cutaneous squamous cell carcinoma (cSCC) with incidental perineural invasion in the primary lesion. Results: There was no recurrence at 5 years in the Perineural Invasion Registry. Basal cell carcinoma (BCC) lesions with nerves <0.1 mm were more commonly treated with surgery alone, compared to lesions with nerves ≥0.1 mm which were offered adjuvant radiotherapy. Of the total BCC lesions with incidental perineural invasion, those with perineural margins ≥5 mm and peripheral tumour margins ≥3 mm were predominantly treated with surgery alone. Eighty‐nine per cent of cSCC lesions with incidental perineural invasion were treated with surgery and adjuvant radiotherapy. Conclusion: Surgery alone is suitable for BCC lesions with incidental perineural invasion. The majority of BCC lesions achieved ≥5 mm perineural and ≥3 mm peripheral tumour margins. Future research can guide if adjuvant radiation is required for BCC with perineural invasion. The treatment of cSCC with incidental perineural invasion with surgery alone remains undetermined.